Pembinaan Sumber Daya Manusia Melalui Pendidikan dan Pelatihan dalam Meningkatkan Kinerja Pegawai Negeri Sipil (Studi pada Kantor BPTP Jawa Timur Di Malang ) - Willy Tri Hardianto (Jurnal Aplikasi Manajemen, 2012)
Government’s official (PNS) of BPTP East Java plays an important role in government’s organizational development; therefore improvement of public service needs to be continued along with technology development. This study was aimed to describe training and education programs undergone by PNS of the BPPTP and their impact on job performance of the PNS, as a part of human resource management program run by the BPPTP. Research method used was qualitative approach, with research focus was to figure up the existing situation of the BPPTP employees to evaluate the implementation of education and trainings programs directed to BPPTP staff. Results of this study showed that training and education is still needed in for upgrading of the BPTP staff.Keywords: government’s official (PNS), Education,Training, Job Performance